Upregulation of TMEM16A Protein in Bronchial Epithelial Cells by Bacterial Pyocyanin - Caci, Emanuela (PLoS One, 2015)
Induction of mucus hypersecretion in the airway epithelium by Th2 cytokines is associated with the expression of TMEM16A, a Ca(2+)-activated Cl(-) channel. We asked whether exposure of airway epithelial cells to bacterial components, a condition that mimics the highly infected environment occurring in cystic fibrosis (CF), also results in a similar response. In cultured human bronchial epithelial cells, treatment with pyocyanin or with a P. aeruginosa culture supernatant caused a significant increase in TMEM16A function. The Ca(2+)-dependent Cl(-) secretion, triggered by stimulation with UTP, was particularly enhanced by pyocyanin in cells from CF patients. Increased expression of TMEM16A protein and of MUC5AC mucin by bacterial components was demonstrated by immunofluorescence in CF and non-CF cells. We also investigated TMEM16A expression in human bronchi by immunocytochemistry. We found increased TMEM16A staining in the airways of CF patients. The strongest signal was observed in CF submucosal glands. Our results suggest that TMEM16A expression/function is upregulated in CF lung disease, possibly as a response towards the presence of bacteria in the airways.